BUILDING COOPERATIVE BUSINESS MODELS IN AGRICULTURE - T. Turlakova (Trakia Journal of Sciences)
Cooperative models are a specific form of successful business. In their activity, they refer to specific principles and values, and due to their democratic structure, they contribute to socio-economic development, provide employment, help to satisfy the needs of their members and clients. Due to their unique business model, cooperatives manage to adapt and respond more effectively to economic, market and financial challenges. The numerous advantages of the cooperative business model are a prerequisite for its transformation into a condition for sustainable regional development. On the other hand, the lack of detailed information on cooperatives limits the possibility of a detailed assessment regarding the size and influence of these structures. The purpose of this report is to reveal the prerequisites for building cooperative business models in agriculture, to indicate their main characteristics and condition, as well as to outline the main prospects for their development.